2022
DOI: 10.1136/bmjresp-2022-001255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a home-based inspiratory muscular training programme on functional capacity in patients with chronic COVID-19 after a hospital discharge: protocol for a randomised control trial (InsCOVID trial)

Abstract: IntroductionExercise intolerance and fatigue are the most common symptoms in patients with chronic COVID-19 after hospital discharge. Supervised exercise training programmes improve symptoms, but scarce research has been done on home-based exercise programmes on the maximal functional capacity for discharged symptomatic COVID-19 patients. This study evaluates whether a home-based inspiratory muscle training (IMT) programme improves maximal functional capacity in chronic COVID-19 after hospital admission.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The exercise programs that combine aerobic and anaerobic exercise [41,44], inspiratory muscle training [22,41], and diaphragmatic breathing [42] contributed to significant improvements in the exercise group after inspiratory muscle training programs [47]. On the contrary, when inspiratory muscle training was only applied, no significant improvement was reported for the intervention group compared to the control group [41,48].…”
Section: Discussionmentioning
confidence: 99%
“…The exercise programs that combine aerobic and anaerobic exercise [41,44], inspiratory muscle training [22,41], and diaphragmatic breathing [42] contributed to significant improvements in the exercise group after inspiratory muscle training programs [47]. On the contrary, when inspiratory muscle training was only applied, no significant improvement was reported for the intervention group compared to the control group [41,48].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Digital Material 3 (Supplementary Table III) 39 - 91 shows the characteristics of the included studies. More than half of the studies (57%, N=30, 2075 participants) included adults with PCC, 42 - 46 , 48 - 51 , 53 , 56 , 57 , 59 - 62 , 64 , 66 , 67 , 70 - 72 , 74 - 76 , 81 , 83 , 85 , 88 , 89 followed by adults with non-severe (34%, N.=18, 1489 participants), severe (6%, N.=3, 230 participants) 39 , 63 , 86 and critical COVID-19 (4%, N.=2, 88 participants). 41 , 90 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…Only 11 RCTs 46 , 55 , 61 , 62 , 64 , 66 , 67 , 74 , 79 , 80 , 85 were similar enough to be grouped within the same comparisons, but the risk of bias across these studies was high and unclear in most of the bias domains. Consequently, we did not pool the data in a meta-analysis but synthesized the evidence narratively.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in QoL, exercise tolerance and haemodynamic function was also reported following a home-based physical activity intervention in middle-aged to older individuals with heart failure [ 25 ]. More recently, studies have shown that home-based physical activity intervention improves exercise capacity and enhances recovery and QoL in COVID-19 survivors [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%